2023
DOI: 10.1007/s00415-023-11679-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome after decompressive hemicraniectomy for malignant middle cerebral artery infarction

Abstract: Background Although decompressive hemicraniectomy (DHC) is a lifesaving treatment strategy for patients with malignant middle cerebral artery infarction (mMCAi), only one in four patients achieves low to moderate post-stroke disability according to previous studies. However, the short follow-up periods in prior studies could have overestimated the poor clinical prognosis. This study therefore examined the long-term outcome after DHC for mMCAi. Methods We r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Then, motor impairments may influence this result. Several studies on stroke have observed that the physical summary is altered ( 6 , 9 , 10 , 12 , 22 24 ). We also determined lower scores in physical subscales compared with the general population, but no patient with MCA infarction was enrolled in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Then, motor impairments may influence this result. Several studies on stroke have observed that the physical summary is altered ( 6 , 9 , 10 , 12 , 22 24 ). We also determined lower scores in physical subscales compared with the general population, but no patient with MCA infarction was enrolled in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider the time from DC to the completion of the survey since several studies report short-term QoL ( 7 , 10 , 27 ). Neurological recovery after a life-threatening event is faster initially but may last for more than 1 year, so early evaluation may not represent health for the rest of their lives ( 9 ). We only included patients with a minimum follow-up of 1 year; the median time elapsed from the event to the outcome assessment was almost 4 years (47 months; IQR 21.5–67.5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations